Children's critical reading skills. Between theory and practice - Patrycja Brudzińska (Rozprawy Społeczne)
Abstract The paper presents the theoretical findings regarding children's critical reading skills. The articlecle also presents the Four Resources Model (Peter Freebody, Allan Luke) as a proposal to work with the text as part of critical literacy. Referring to the results of international research on progress in reading PIRLS, it reveals dilemmas related to the teaching of critical reading of the youngest recipients of literary content.